2019
DOI: 10.1007/s11187-019-00296-w
|View full text |Cite
|
Sign up to set email alerts
|

Spillovers from high growth firms: evidence from Hungary

Abstract: How do high-growth firms (HGFs) affect the rest of the economy? We explore this question using Hungarian administrative microdata. Relying on the Birch definition of HGFs, we find evidence for stronger productivity growth for firms operating in industries with more HGFs and for firms supplying industries with more HGFs. Knowledge spillovers or the surge of HGFs' demand for intermediate inputs could explain these positive associations. Firms with intermediate productivity levels seem most likely to benefit from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…These findings are consistent with existing studies which find that fastgrowing new firms, not new firms in general, account for most of the new jobs created by small and medium-sized enterprises in advanced economies. In-depth studies of firm dynamics in selected developing economies in South America, Africa, Asia, and the Middle East reveal that high-growth new firms are not only powerful engines of job and output growth, but they also create positive spillovers for other businesses along the value chain (Grover et al 2019). De Nicola et al (2021 analyzed Hungarian administrative microdata and found evidence for stronger productivity growth for firms operating in industries with more high-growth firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings are consistent with existing studies which find that fastgrowing new firms, not new firms in general, account for most of the new jobs created by small and medium-sized enterprises in advanced economies. In-depth studies of firm dynamics in selected developing economies in South America, Africa, Asia, and the Middle East reveal that high-growth new firms are not only powerful engines of job and output growth, but they also create positive spillovers for other businesses along the value chain (Grover et al 2019). De Nicola et al (2021 analyzed Hungarian administrative microdata and found evidence for stronger productivity growth for firms operating in industries with more high-growth firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings are consistent with existing studies which find that fastgrowing new firms, not new firms in general, account for most of the new jobs created by small and medium-sized enterprises in advanced economies. In-depth studies of firm dynamics in selected developing economies in South America, Africa, Asia, and the Middle East reveal that high-growth new firms are not only powerful engines of job and output growth, but they also create positive spillovers for other businesses along the value chain (Grover et al 2019). De Nicola et al (2021 analyzed Hungarian administrative microdata and found evidence for stronger productivity growth for firms operating in industries with more high-growth firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Acs, 2006;Audretsch & Keilbach, 2008;Audretsch Keilbach & Lehmann, 2006;Audretsch & Thurik, 2000;Fritsch and Mueller, 2004;van Stel and Storey, 2004). Indeed, entrepreneurship has been linked to the growth and prosperity of nations, as well as the ability to lead to the sustainable development of various sectors (Dean and McMullen, 2007;Van Stel, Storey, & Thurik, 2007;Shepherd and Patzelt, 2011;Belz and Binder, 2017;De Nicola, Muraközy, & Tan, 2021). Porter for instance, asserted that entrepreneurship is "at the heart of national advantage " (1990: 125).…”
Section: Introductionmentioning
confidence: 99%